2008
DOI: 10.1371/journal.pbio.0060318
|View full text |Cite
|
Sign up to set email alerts
|

PKMζ Maintains Spatial, Instrumental, and Classically Conditioned Long-Term Memories

Abstract: How long-term memories are stored is a fundamental question in neuroscience. The first molecular mechanism for long-term memory storage in the brain was recently identified as the persistent action of protein kinase Mzeta (PKMζ), an autonomously active atypical protein kinase C (PKC) isoform critical for the maintenance of long-term potentiation (LTP). PKMζ maintains aversively conditioned associations, but what general form of information the kinase encodes in the brain is unknown. We first confirmed the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
263
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(291 citation statements)
references
References 53 publications
(95 reference statements)
25
263
3
Order By: Relevance
“…Although previous studies have reported a synaptic insertion of AMPARs at hippocampal and amygdaloid synapses 24 h after auditory fear conditioning 19,42 , there appears to be no increase in dorsohippocampal AMPAR surface expression 1 day after contextual foreground conditioning (without tone) as measured here. This is in line with previous research that showed that disruption of GluA2 surface expression in the hippocampus 1 day after conditioning has no effect on maintenance of contextual fear memory 43,44 , in contrast to the amygdala 43 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although previous studies have reported a synaptic insertion of AMPARs at hippocampal and amygdaloid synapses 24 h after auditory fear conditioning 19,42 , there appears to be no increase in dorsohippocampal AMPAR surface expression 1 day after contextual foreground conditioning (without tone) as measured here. This is in line with previous research that showed that disruption of GluA2 surface expression in the hippocampus 1 day after conditioning has no effect on maintenance of contextual fear memory 43,44 , in contrast to the amygdala 43 .…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous research that showed that disruption of GluA2 surface expression in the hippocampus 1 day after conditioning has no effect on maintenance of contextual fear memory 43,44 , in contrast to the amygdala 43 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, it was shown that injection of ZIP into the hippocampus erases a consolidated spatial LTM (Pastalkova et al 2006). Further, ZIP injection into the basolateral amygdala blocks cued and contextual fear LTM as well as inhibitory avoidance LTM (Serrano et al 2008;Kwapis et al 2009). However, not all memory storage processes are ZIP-dependent (for review, see Glanzman 2013).…”
Section: Pkc Including Pkmzmentioning
confidence: 99%
“…However, not all memory storage processes are ZIP-dependent (for review, see Glanzman 2013). For example, injection of ZIP into the dorsal hippocampus does not affect contextual fear LTM, although this part of the hippocampus is required for contextual LTM (Serrano et al 2008;Kwapis et al 2009). A recent study has claimed that ZIP does not block specifically PKMz .…”
Section: Pkc Including Pkmzmentioning
confidence: 99%